2022
DOI: 10.3389/fendo.2021.782865
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Hypothyroidism as the Most Common Thyroid Dysfunction Status in Children With Down’s Syndrome

Abstract: IntroductionThyroid dysfunctions are one of the most common abnormalities coexisting in children with Down’s syndrome (DS) and have been reported in up to 54% of cases.Aim of the StudyThe purposes of this retrospective study were to investigate the course of subclinical hypothyroidism in children with DS, to evaluate the thyroid function of these subjects in relation to the risk of developing overt thyroid disease and autoimmunity, and to identify clinical and biochemical characteristics of patients prescribed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…The spectrum of thyroid dysfunction includes congenital hypothyroidism, subclinical hypothyroidism, acquired hypothyroidism (autoimmune/non-autoimmune), and hyperthyroidism [12]. Correct functioning of the thyroid gland is very important in the development of any child, especially a child with DS, as it ensures normal physical and mental development [13]. Thyroid diseases also occur in about 20-50% of adults with DS.…”
Section: Introductionmentioning
confidence: 99%
“…The spectrum of thyroid dysfunction includes congenital hypothyroidism, subclinical hypothyroidism, acquired hypothyroidism (autoimmune/non-autoimmune), and hyperthyroidism [12]. Correct functioning of the thyroid gland is very important in the development of any child, especially a child with DS, as it ensures normal physical and mental development [13]. Thyroid diseases also occur in about 20-50% of adults with DS.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies revealed benefits of replacement therapy and normalization of TSH values in terms of growth velocity, height, and head circumference ( 17 , 47 , 48 ); no improvement of motor and cognitive development was found ( 47 ). Besides, most of these results have been systematically challenged by different authors, who did not confirm such findings ( 31 ).…”
Section: Thyroid Functionmentioning
confidence: 96%
“…Levothyroxine dosage is titrated, until biochemical euthyroidism is achieved. Though an average dosage of 1-2 mcg/kg/day is usually sufficient in the general population, daily doses ranging from 0.3 to 6.6 mcg/kg have been reported in children and adolescents with DS ( 31 ). The first evaluation of efficacy by assessing thyroid function tests is indicated not earlier than 6 to 8 weeks following treatment prescription and then every six months ( 32 ).…”
Section: Thyroid Functionmentioning
confidence: 99%
“…For example, higher rates of hypothyroidism have been documented, with estimated prevalence of 23.5% in pediatric age and 39-61% in adult age (Carroll et al, 2008;Tsou et al, 2020). Another thyroid dysfunction particularly frequent in DS is SH, whose prevalence in this population has been estimated up to 87% (O' Grady and Cody, 2011;Szeliga et al, 2022), remarkably higher than the prevalence reported in general population (5%) (Chiovato et al, 2019). SH diagnosis is possible when serum thyroid-stimulating hormone (TSH) is slightly elevated and the levels of total or free thyroxine and triiodothyronine are normal (O'Grady and Cody, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that the increased prevalence of thyroid dysfunctions in youth with DS could be determined by a delayed maturation of the hypothalamic–pituitary-thyroid axis; this would result in a temporary process not necessitating treatment ( Sharav, 1988 , 1991 ). Accordingly, literature suggests that only a limited percentage of individuals with DS and SH develops an overt hypothyroidism, particularly females with mostly positive titer of antithyroid autoantibodies ( Szeliga et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%